Penyelesaian Project dan Pemberian Scaffolding dalam Pembelajaran Project Based Learning (PBL) Di Perguruan Tinggi - Zaini Zaini (JSHP : Jurnal Sosial Humaniora dan Pendidikan, 2018)
Students are people who have been in adolescence/early adulthood who have the ability to think formally, and to regulate their needs and play an active role through social interaction. Learning in higher education needs to cover the development of thinking so that the standard of graduate competence can be achieved. The beginning of project based learning (PBL) was adopted more slowly in higher education and in its development. It was recommended to adopt PBL because PBL has the potential to improve learning and be able to develop optimally academic skills, occupational skills, employ ability. This study is intended to uncover the process of project completion and explain the level of scaffoding that can be given during project completion from students who have low abilities . The research approach used is qualitative researchThe results of the study indicate that the project can be completed even though it takes a long time from the project completion plan.Scaffolding levels include environmental provisions, explaining, reviewing, and restructuring and developing conceptual thinking.